Health and health care in South Africa in transition: a macro perspective - Dingie van Rensburg (Acta Academica)
The South African health care system, along with society in general, is undergoing profound transformation. Afcer almost five years, questions may well be posed about the nature of chis transition, the benefits of the reform for health care, and the effects of the transformation on the health and well-being of the population. The argument is chat reform of a fundamental nature has indeed taken place in numerous dimensions of the health sphere. However, crucial aspects of the health system remain unchanged. Regarding the effects of the transition on the health and wellbeing of the population, one may certainly assume char significant gains have been achieved as a result of the reform measures, although practice thus far also adduces some evidence co che concrary.